Psychometric properties of the German version of the Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS) - Biermann, Miriam; Bohus, Martin; Gilbert, Paul; Vonderlin, Ruben; Cornelisse, Sven; Osen, Bernhard; Graser, Johannes; Bruene, Martin; Ebert, Andreas; Kleindienst, Nikolaus; Lyssenko, Lisa (Psychological assessment, 2021)
Self-criticism is significantly associated with a variety of mental health difficulties affecting vulnerability, presentation, progress, and recovery. In contrast, self-reassurance is associated with good mental health, psychological well-being, and beneficial physiological processes. The 22-item Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS) is an internationally used self-report questionnaire for measuring manifestation and changes in different types of self-criticism and self-reassurance. It has been shown to be a valid and reliable measure in clinical and nonclinical samples. In the present study, a German translation of the FSCRS and its 3 subscales (hated self, inadequate self, reassured self) was provided, and the factor structure and psychometric properties were examined in 415 participants from 4 different population samples: (a) a sample from the general population, (b) a sample of psychiatric residential and outpatients, (c) a clinical sample of residential and outpatients with a primary diagnosis of borderline personality disorder (BPD), and (d) a sample of healthy control participants. Results from confirmatory factor analysis favored a 3-factor solution of the German FSCRS. Furthermore, findings indicate that the German version of the FSCRS and its subscales had good to excellent internal consistencies. Convergent validity was good for all 3 subscales as shown by medium to large correlations with established measures of self-criticism, self-compassion, self-esteem, satisfaction with life, symptoms of depression and anxiety, and secure attachment styles. Additionally, the 3 FSCRS subscales discriminated significantly between the clinical and nonclinical samples, with the BPD sample demonstrating significantly higher levels than the other samples on the hated self subscale.